O cuidador de portadores de necessidades especiais em assistência odontológica - Aquino, Diolinda Júlia Nascimento de (2006)
The present study, of a descriptive-analytical character, aimed to identify the 35 people with special needs in dental care in a dental specialty clinic, and their respective caregivers and to characterize the involvement of the caregiver of the special needs with dental care offered. The data were obtained through an interview script containing closed and open questions. The results from the identification data and the speeches of the caregivers pointed to people with special needs between one and 45 years old, with little variation between ages, the majority being female (54.3%). The origin was linked to some municipalities of DIR IX (Barretos) and DIR XIII (France). No person with a special need carried out any type of formal work as an occupation, showing a clientele dependent on someone or some kind of financial resource. All people with special needs had a diagnosis of mental disability, being exclusive in 31.4%, or associated with other disorders such as neuromotor (34.3%), genetic alterations (8.6%) and physical disability (2.9% ). Some patients (42.8%) had previously received dental assistance, offered by APAE (65.0%) or by clinics linked to faculties of dentistry (25.0%). Regarding caregivers, the age ranged from 15 to 70 years, with 68.9% between 15 and 45 years. The caregivers were also, in the great majority (97.1%) female, whose degree of kinship was by people of the closest contact with people with special needs (mother, sister, father, aunt). Through the speeches, the various reasons for being a caregiver were verbalized, related to the fact of being a mother, and accompanied by feelings of selflessness, donation, altruism, resignation, closeness, among others. No caregiver receives any type of fee for the function. All of them considered dental assistance important for people with special needs, and the difficulties they faced were related to the difficulty of transportation, opening hours, not knowing how to deal with disabilities and fear of sedation. All caregivers verbalized the receipt of guidance about some aspects related to the dental care offered and some related certain difficulties faced about the received instructions. 91.4% of the caregivers verbalized the collaboration of the person with special needs for the implementation of the guidelines and the others referred to the need to adopt some forms of differentiated awareness (toys, stories and music). Caregivers manifested some noticeable changes in the behavior of people with special needs and the need for personal renunciation for having assumed the role of caregiver. The caregivers' view of their role during dental care ends with the discussion of these anonymous heroes who deserve recognition of their role not only in the family, but mainly in the social sphere.